Analysis Of The Effect Of Brand Image On The Sales Volume Of Three Products - Nur Arifiya Arifiya; Aliffia Teja Prasasty Teja Prasasty; Rina Nurhidayati Nurhidayati (Faculty of Economics and Business, Universitas Malikussaleh, 2021)
Brand image is one of the essential things that must be considered for maintaining the existence of a product. A positive brand image is expected to provide trust and satisfaction’s consumer for the product. It will undoubtedly have an impact on increasing the number of product uses by the customer. The purpose of this study was to analyze the effect of brand image on product sales volume. The sampling technique in this study was random cluster sampling. Meanwhile, the analysis method used is Analysis of Variance (ANOVA). The results of the research that have been done show that there is an effect of brand image on sales volume. It can be a material consideration for the company to continue building a brand image to optimize product sales volume.